Metaverse Peluang Atau Ancaman Bagi Umkm di Indonesia Pada Sektor Industri Pariwisata - Rizki Nurul Nugraha; Farrah Puspita F (Peneliti.net, 2023)
This research is a literature study that discusses the Metaverse Opportunities or Threats for Small and Medium Enterprises (SMEs) in the Tourism Industry. In this research study, theory is used in entrepreneurial activities. The business in this research focuses on business feasibility and business growth in entrepreneurial activities. The research findings indicate the importance of using business theories in business feasibility and business growth. An interesting further research that can be developed is the Analysis of Human Resource Theory in Business for Entrepreneurial Activities.